Risk Policies in the United States: Definition and Characteristics Based on a Scoping Review of the Literature. Issue 5 (16th December 2014) - Jacob, Steve; Schiffino, Nathalie
<x xml:space="preserve">Abstract</x> The concept of "risk policy" is used with increasing frequency by decisionmakers, researchers, and the media. However, there is no precise, generally accepted definition of what is covered by policies in this area. Based on a scoping review of the literature published in key journals in the sector, we have identified the main characteristics of public risk policies drawn up and implemented in the United States. The sample comprised 21 articles published in six multidisciplinary journals between 2000 and 2010.